Kajian Ruang Publik Terbuka dan Tertutup dengan Prinsip Eco-Design di Kawasan Kotabaru, Yogyakarta - Tsumasabilla, Cut Nushaimah; Karang, Anak Agung Ayu Ratih Tribhuana Adityadewi; Wijayanti, Maria Rosari (ARCHIHUMANUM, 2025)
Kotabaru is a Dutch heritage area that has now changed into a functional area consisting of educational, commercial, and social places, with quite high mobility. However, this area still has a lack of green open space, so it still needs development related to open space that can be used as a place for public interaction. Therefore, a redesign of open space is needed. This journal aims to develop an eco-design concept that can be used as one of the considerations to improve the comfort of space in Kotabaru, by considering the need for green open space and social interaction. With the existence of this public facility, it is hoped that it can be a place for socializing and help add green space to the Kotabaru area. This research was conducted using qualitative research methods and descriptive explanations by mapping the distribution of public space and sampling public space.